Latest Tournaisian–late Viséan foraminiferal biozonation (MFZ8–MFZ14) of the Valiabad area, northwestern Alborz (Iran): geological implications. (22nd October 2014) - Zandkarimi, Keyvan; Najafian, Bahram; Vachard, Daniel; Bahrammanesh, Maryamnaz; Vaziri, Seyed Hamid
Abstract : The Mobarak Formation in the Valiabad area (northwestern Alborz, Iran) is composed of bioclastic, oolitic and sandy limestone interbedded with black shale, and is disconformably underlain and overlain by the Cambrian Lalun and Permian Dorud formations, respectively. In this study, 104 foraminiferal species belonging to 12 families and 33 genera were determined. Among them, six genera and nine species are reported for the first time in Iran. Analysis of the foraminiferal assemblages has identified eight local biozones, which can be correlated with the MFZ8 to MFZ14 zones of the Viséan stratotypes in Belgium. The Valiabad equivalents of these biozones are essentially characterized by (1) Eoparastaffella ex gr. rotunda ‐' florigena '– Lysella cf. gadukensis ; (2) Eoparastaffella simplex–Lapparentidiscus bokanensis ; (3) Ammarchaediscus ; (4) Uralodiscus–Glomodiscus ; (5) Glomodiscus–Archaediscus ; (6) Pojarkovella–Mstinia fallax ; (7) Mstinia bulloides–Pseudoendothyra ; and (8) Howchinia gibba–Howchinia bradyana–Tubispirodiscus attenuatus . Consequently, the Valiabad section appears to be one of the most complete Viséan sections in Iran. Some taxonomic precisions are provided about the principal taxa. Biogeographically, (1) the MFZ8–MFZ11 biozones are extended to all the shelves of the Palaeotethys (from Ireland to South China) and Urals oceans; nevertheless, due to the complete evolution of archaediscoids, they seem more related to the Perigondwanan assemblages from Sinai and Taurus (including the Antalya Nappes); (2) the MFZ12 assemblage appears relatively endemic; and (3) the impoverished assemblages of the biozones MFZ13‐14 have marked affinities with the Kazakhstan Block. It is currently impossible to indicate precisely if these variations are related with a drift of the Alborz region to the north, or to a change of oceanic currents. Moreover, the double affinity highlights the narrowness of the Palaeotethys in Iran during the Viséan. Copyright © 2014 John Wiley & Sons, Ltd.